PERTANIAN ORGANIK BERBASIS PUPUK BOKASHI UNTUK PENINGKATAN PRODUKTIVITAS CABAI PADA KELOMPOK TANI DI KABUPATEN MERAUKE - Patawaran, Nilfred; Nggego, Dedi Abdianto; Tanggu Redu, Silas (Jurnal Abdimas Bina Bangsa, 2025)
The productivity of chili plants is closely related to fertilization. Scarcity and relatively expensive fertilizer prices are a problem for chili farmers in Merauke Regency. Therefore, amidst the intensive use of chemical fertilizers, availability and price constraints, organic bokashi fertilizer is a more environmentally friendly and sustainable alternative. Bokashi is an organic fertilizer that is important in improving soil structure, providing complete nutrition slowly and sustainably, stimulating the activity of soil microorganisms, and reducing dependence on chemical fertilizers. Another problem is that farmers still experience limited knowledge regarding the management of local resources (livestock and agricultural waste) which are abundant around the location. This training activity on processing organic bokashi fertilizer for chili farmers in Merauke Regency aims to increase farmers' knowledge and skills in cultivating chili plants organically. PkM was implemented in the Semangga Jaya Village Chili Farmers Group, Semangga District, Merauke Regency. This activity lasts for 1 month starting from preparation activities, implementation (socialization and training), as well as evaluation and program sustainability. PkM's core activity is making bokashi fertilizer based on Effective Microorganisms Technology (EMT). The methods used in implementing this service are survey methods, hearings, and demonstration plots. The results of the training showed that farmers gained the skills to make EMT-based bokashi organic fertilizer by utilizing organic waste. Farmers then adopt environmentally friendly agricultural technology in cultivation activities to increase soil fertility and productivity of chili plants.